On boundary integral equations of the second kind for symmetric regions - Murid, Ali H.M.; Razali, Mohd. R.M (Jabatan Matematik, Universiti Teknologi Malaysia, 1995)
We determine conditions for which a complex boundary integral equation for symmetric regions can be rewritten in a form that would lead to a small system of equations thus allowing a reduction of computing time. The results are then applied to the Kerzman-Stein integral equation which appears in the problem of conformal mapping of a simply connected domain to a unit disk.